Book Review of Growing Up with Domestic Violence - Corkum-O'Grady, Lisa (Canadian Journal of Counselling and Psychotherapy, 2012)
Growing Up with Domestic Violence examines the progress made over the last 20 years by those working with children who have been exposed to intimate partner violence within their families. The authors expertly demonstrate why it is crucial for clinicians to possess an understanding of the consequences of exposure and to develop effective assessment and intervention skills. Along with a review of relevant research, assessment considerations, and current theories, clinicians are provided with an exploration of practical, evidence-based treatment guidance. These guidelines include suggestions around methods of treatment for both individual and group intervention. Barriers to carrying out treatment are addressed, as well as efficacy and prognosis after intervention. Growing Up with Domestic Violence offers a good combination of research, theory, and clinical information in a easy-to-read and very concise format.